[tex]\Large\boxed{\begin{array}{l}\tt a)\\\begin{cases}\sf x+y=22\\\sf x-y=8\end{cases}\\\begin{cases}\sf y=22-x\\\sf x-y=8\end{cases}\\\sf x-(22-x)=8\\\sf x-22+x=8\\\sf 2x=8+22\\\sf 2x=30\\\sf x=\dfrac{30}{2}\\\\\sf x=15\\\sf y=22-x\\\sf y=22-15\\\sf y=7\\\sf S=\{15,7\}\blue{\checkmark}\end{array}}[/tex]
[tex]\Large\boxed{\begin{array}{l}\tt b)\\\begin{cases}\sf 2x+y=26\\\sf x-y=4\end{cases}\\\\\begin{cases}\sf 2x+y=26\\\sf y=x-4\end{cases}\\\sf 2x+x-4=26\\\sf 3x=4+26\\\sf 3x=30\\\sf x=\dfrac{30}{3}\\\\\sf x=10\\\sf y=x-4\\\sf y=10-4\\\sf y=6\\\sf S=\{10,6\}\blue{\checkmark}\end{array}}[/tex]
[tex]\Large\boxed{\begin{array}{l}\tt c)\\\begin{cases}\sf3x+y=-5\\\sf5x-2y=-1\end{cases}\\\\\begin{cases}\sf y=-3x-5\\\sf 5x-2y=-1\end{cases}\\\sf 5x-2\cdot(-3x-5)=-1\\\sf 5x+6x+10=-1\\\sf 11x=-1-10\\\sf 11x=-11\\\sf x=-\dfrac{11}{11}\\\\\sf x=-1\\\sf y=-3x-5\\\sf y=-3\cdot(-1)-5\\\sf y=3-5\\\sf y=-2\\\sf S=\{-1,-2\}\blue{\checkmark}\end{array}}[/tex]
[tex]\Large\boxed{\begin{array}{l}\tt d)\\\begin{cases}\sf x+2y=-4\\\sf3x-2y=20\end{cases}\\\\\begin{cases}\sf x=-2y-4\\\sf 3x-2y=20\end{cases}\\\sf 3\cdot(-2y-4)-2y=20\\\sf -6y-12-2y=20\\\sf 6y+2y=-12-20\\\sf 8y=-32\\\sf y=-\dfrac{32}{8}\\\\\sf y=-4\\\sf x=-2y-4\\\sf x=-2\cdot(-4)-4\\\sf x=8-4\\\sf x=4\\\sf S=\{4,-4\}\blue{\checkmark}\end{array}}[/tex]